2008
DOI: 10.1111/j.1523-1739.2008.00993.x
|View full text |Cite
|
Sign up to set email alerts
|

Key Role of European Rabbits in the Conservation of the Western Mediterranean Basin Hotspot

Abstract: The Mediterranean Basin is a global hotspot of biodiversity. Hotspots are said to be experiencing a major loss of habitat, but an added risk could be the decline of some species having a special role in ecological relationships of the system. We reviewed the role of European rabbits (Oryctolagus cuniculus) as a keystone species in the Iberian Peninsula portion of the Mediterranean hotspot. Rabbits conspicuously alter plant species composition and vegetation structure through grazing and seed dispersal, which c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
177
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 236 publications
(182 citation statements)
references
References 77 publications
2
177
0
3
Order By: Relevance
“…The scarcity of the main food resources exploited by the griffon vultures (predictable large carcasses) would lead to an increase in indirect competition with subordinate species for small and medium-sized carcasses, in a process similar to the hyperpredation observed in predator-prey systems (Courchamp et al 2000). In the Iberian Peninsula the carcasses of wild rabbits are heavily exploited by facultative predators and carrion-eaters (Delibes-Mateos et al 2008) and for some threatened species like the Egyptian vulture, the cinereous vulture (Aegypius monachus) and the bearded vulture (Gypaetus barbatus) constitute an essential part of the diet during the breeding period (Hiraldo 1976;Donázar and Ceballos 1988;Margalida et al 2009). In a field experiment carried out during 2005 and 2006, when the availability of large carcasses was still high, we observed that 30% of the wild rabbit carcasses were consumed by griffon vultures, which displaced other species like Egyptian vultures, red kites (Milvus milvus), black kites (Milvus migrans), marh harriers (Circus aeruginosus), common European buzzards (Buteo buteo), and common ravens (Corvus corax).…”
Section: Discussionmentioning
confidence: 99%
“…The scarcity of the main food resources exploited by the griffon vultures (predictable large carcasses) would lead to an increase in indirect competition with subordinate species for small and medium-sized carcasses, in a process similar to the hyperpredation observed in predator-prey systems (Courchamp et al 2000). In the Iberian Peninsula the carcasses of wild rabbits are heavily exploited by facultative predators and carrion-eaters (Delibes-Mateos et al 2008) and for some threatened species like the Egyptian vulture, the cinereous vulture (Aegypius monachus) and the bearded vulture (Gypaetus barbatus) constitute an essential part of the diet during the breeding period (Hiraldo 1976;Donázar and Ceballos 1988;Margalida et al 2009). In a field experiment carried out during 2005 and 2006, when the availability of large carcasses was still high, we observed that 30% of the wild rabbit carcasses were consumed by griffon vultures, which displaced other species like Egyptian vultures, red kites (Milvus milvus), black kites (Milvus migrans), marh harriers (Circus aeruginosus), common European buzzards (Buteo buteo), and common ravens (Corvus corax).…”
Section: Discussionmentioning
confidence: 99%
“…We address this key limitation using coupled ecological nichepopulation models with source-sink dynamics 6,7 , simulating the stochasticdemographicresponsesofIberianlynxto:spatialpatterns of rabbit abundance conditioned by disease, climate and landuse variation; and changes in climate suitability and landscape modification. We consider the interaction between rabbits and Iberian lynx as unidirectional, because lynx are extremely rare, whereas rabbits are abundant and have greater than 30 vertebrate predators,many ofthem widelydistributed andlocally abundant 15 . Rareeffortstoaccountforspeciesinteractionsinclimate-ecological forecasts have used overly simple approaches; by adding an interactingspeciesasanadditional predictorinacorrelativemodel, or by restricting the distribution of one species to the modelled distribution of the other 16 .…”
mentioning
confidence: 99%
“…Within its native range, rabbits are the preferred prey for most of the Iberian vertebrate predators and therefore, a species of conservation concern (Delibes‐Mateos et al., 2008; Virgós, Cabezas‐Díaz, & Lozano, 2007). Meanwhile, in other areas of the world, rabbits are invasive species that spread quickly in new environments, causing severe damage to the ecosystems they invade (Lees & Bell, 2008).…”
Section: Introductionmentioning
confidence: 99%